Compaction Control Using Degree of Saturation and Plasticity Index on Tropical Soil - Hasbullah Nawir; Laras Dipa Pramudita; Tita Kartika Dewi; Dayu Apoji; Sugeng Krisnanto (Journal of Engineering and Technological Sciences, 2023)
Soil compaction in the field is conventionally controlled using maximum dry density, (ρd)max, and optimum moisture content, (w)opt, as the target properties. However, achieving accurate control of these target properties can be difficult due to variation of compaction energy level (CEL) and soil type. Recently, a novel soil compaction control approach using optimum degree of saturation, (Sr)opt, as the target properties has been proposed. It was argued that (Sr)opt can be a better compaction control property as the value is less sensitive to the variation of CEL and soil type. This paper presents an investigation of the compaction characteristics of tropical soils from several locations in Indonesia based on both primary and secondary data. This study was performed by exploring the relationships between (i) dry density (ρd) and Sr, (ii) (ρd) and plasticity index (PI), (iii) (ρd) and CBR, as well as (iv) (ρd) and permeability. This study showed that the (Sr)opt of the soils was 91.2%, with variation between 81.2% and 96.5%. This study also showed that (ρd)max can be related to PI at a given CEL. It is expected that the proposed relationships can be better references for field compaction control practices in Indonesia.